On the Genesis of Intellectual Crossroads: Early Fragmentation in the Formation of Modern Indonesian Intelligentsia - Yudi Latif (Studia Islamika, 2004)
This article is an inter-textual analysis of the early colonial and capitalist driven implantation of a western education system and its subsequent influence on the way of thought of the East Indies new elite. Such a feature will be juxtaposed with the impacts of the deepening penetration of colonialism and capitalism on the continuity and discontinuity of historical Islam.DOI: 10.15408/sdi.v11i1.653